PERBANDINGAN KEWAJIBAN NAFKAH MENURUT HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Nandang Fathur Rahman (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2022)
Domestic life is regulated, either in Islamic teachings or in statutory law. A person provides a living on the basis of marriage ties. The obligation to provide a living by the husband is an obligation that must be fulfilled. On this basis, the question arises what is the obligation to earn a living according to Islamic law and legislation in Indonesia, and what is the legal basis used in the obligation to earn a living. This research was conducted using a descriptive method whose data were obtained from a literature study with a qualitative approach. The purpose of this study is to describe simply the obligation of living according to Islamic law and legislation in Indonesia, then the legal basis used in the obligation of living. The results of the study found that living is a right that must be fulfilled by a husband to his wife and children, both clothing, food, and housing. Islamic law explains that the obligation to make a living includes the fulfillment of physical and spiritual expenses, as well as the husband's ability to earn a living. According to positive law, the obligation to make a living is regulated in Law no. 1 of 1974 concerning Marriage and in the Compilation of Islamic Law.